The role of human resource governance in behavior modeling: Applied research in Baghdad Teaching Hospital - Saba Taleb Wahab,; Ali Razaq Al-Abedi, (International Journal of Psychosocial Rehabilitation, 2020)
The main purpose of this research is to identify the importance of the role played by human resources governance in modeling their behaviors, as it is possible through governance to define a set of criteria and indicators that are adopted in determining the nature of acceptable behaviors when implementing activities and tasks assigned to human resources within the organization, as the research problem indicates Decreased knowledge awareness and conceptual perception among the respondents of the importance of employing the dimensions of human resources governance in modeling their behaviors, and therefore the importance of research emerges in providing a set of treatments that would limit the impact of this problem, while the objectives of the research were represented in the research attempt to determine the reality of applying the variables discussed and from Then test the relations between them within the organization field of application. The descriptive analytical approach was adopted in the application of this research in order to conform to its objectives, as the questionnaire was adopted in data collection, which was prepared according to a number of criteria and ready-made indicators, which were distributed to a sample of (163) specialists in Baghdad Teaching Hospital, and after data processing using a number of The statistical tools available in the ready statistical program (SPSS), a number of results were reached, which confirmed a positive correlation between the variables discussed and the significance of their impact, so the assumptions from which the research was launched were accepted, and on the basis of that the research concluded that there is an actual application of the variables discussed within the organizations in the field of application Despite the low awareness of its knowledge, it was recommended that a set of training courses and seminars should be prepared that enhance the knowledge of human resources within the research organization and as far as the issue of human resource governance and behavior modeling is concerned.